2013
DOI: 10.1002/grl.50360
|View full text |Cite
|
Sign up to set email alerts
|

More hurricanes to hit western Europe due to global warming

Abstract: [1] We use a very high resolution global climate model (~25 km grid size) with prescribed sea surface temperatures to show that greenhouse warming enhances the occurrence of hurricane-force (> 32.6 m s -1 ) storms over western Europe during early autumn (August-October), the majority of which originate as a tropical cyclone. The rise in Atlantic tropical sea surface temperatures extends eastward the breeding ground of tropical cyclones, yielding more frequent and intense hurricanes following pathways directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
199
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(211 citation statements)
references
References 24 publications
11
199
1
Order By: Relevance
“…No change in the likelihood is found for DJF. Consistent with our findings, a larger ensemble of CMIP5 models shows no significant change in rainfall over the United Kingdom during cold seasons until the second half of the century, when wet winters are projected to increase in frequency (van Oldenborgh et al 2013).…”
Section: S49supporting
confidence: 90%
See 2 more Smart Citations
“…No change in the likelihood is found for DJF. Consistent with our findings, a larger ensemble of CMIP5 models shows no significant change in rainfall over the United Kingdom during cold seasons until the second half of the century, when wet winters are projected to increase in frequency (van Oldenborgh et al 2013).…”
Section: S49supporting
confidence: 90%
“…8.2e,f). Future projections show a continuation of this general pattern, but given the large spread between models, scenarios, and seasons, it is possible the wet-dry boundary will shift leaving São Paulo's precipitation future uncertain (van Oldenborgh et al 2013). Hence, while the recent drought impacts were most likely not driven by an increase in hydrometeorological hazard, there is a risk that this may not hold in an even warmer world.…”
Section: Referencesmentioning
confidence: 97%
See 1 more Smart Citation
“…nesting a high-resolution RCM in a lowresolution GCM, is a potential alternative, yet at the comparatively coarse resolutions that are currently feasible for the driving GCM, e.g. N96 resolution with 19 vertical levels in the weather@home system (Massey et al, 2015), concerns remain over the ability of the modelling system to represent critically important processes such as mid-latitude circulation regimes (Dawson et al, 2012) or tropical cyclones undergoing extratropical transition (Haarsma et al, 2013). For other applications the assessment will be more positive.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shed some light on this debate. Using a high resolution (~25 km grid size) global climate model, Haarsma et al (2013) showed that the frequency of hurricane-force storms are projected to increase considerably in Europe by the end of the twenty-first century. They suggested that higher SSTs and extension of the hurricane breeding ground imply that tropical cyclones under these future conditions are likely to have experienced less dissipation in their northward propagation when reaching the midlatitudes, thereby facilitating reintensification through merging with a baroclinic wave.…”
Section: Introductionmentioning
confidence: 99%